The moderating role of corporate governance on the relationship between a firm’s product lifecycle and risk-taking - Namazi, Mohammad; Hosseini-Nia, Somayyeh (Penerbit Universiti Kebangsaan Malaysia, 2017)
Management accounting theories claim that firms experience different risks during different stages of a product’s lifecycle. This study examines the moderating role of corporate governance on the relationship between a firm’s product lifecycle and its risk- taking aspects. The study was conducted from 2006 to 2014 in the Tehran Stock Exchange. We conducted a statistical panel data analysis and the sample consisted of 128 firms (1,152 firm-year observations). The results showed that the decline stage of the product life cycle is the only stage that would affect the risk-taking of the selected firms. Conceivably, there is a positive relationship between the decline stage of the product lifecycle and risk-taking. In addition, the results indicate a positive relationship between the growth and decline stages of a firm’s product lifecycle and its risk-taking when corporate governance plays a moderating role. In short, when corporate governance acts as a moderating variable, the relationship between a firm’s product lifecycle and its risk-taking is lower than the time when there is no such variable. Hence, regulators and managers should consider the role of corporate governance in all the stages of a product’s lifecycle to ensure successful firm decisions and strategies.